2022
DOI: 10.3390/foods11182880
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Suitability of Tea Cultivars for Processing Oolong Tea from the Perspective of Aroma Based on Olfactory Sensory, Electronic Nose, and GC-MS Data Correlation Analysis

Abstract: The oolong tea aroma is shown to consist of cultivar aroma and technical aroma in this study based on the aroma differences between oolong tea products of cultivars of different suitability, as determined by correlation analysis of olfactory, sensory, electronic nose, and GC-MS data. Human senses were significantly affected by the aroma components, which included eight terpene metabolites (β-Ocimene, (Z)-Furan linalool oxide, linalool, (3E)-4,8-Dimethyl-1,3,7-nonatriene, (E)-Pyranoid linalool oxide, γ-Elemene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…In recent years, electronic noses and electronic tongues have been widely used for the analysis of taste, which are feasible to determine tea quality. 22,23 As shown in Fig. 1A, in principal component analysis (PCA), the first two components PC1 and PC2 accounted for 99.99% (PC1 = 99.92% and PC2 = 0.07%), indicating that the tea samples of FBT and MFBT could clearly be discriminated.…”
Section: Resultsmentioning
confidence: 93%
“…In recent years, electronic noses and electronic tongues have been widely used for the analysis of taste, which are feasible to determine tea quality. 22,23 As shown in Fig. 1A, in principal component analysis (PCA), the first two components PC1 and PC2 accounted for 99.99% (PC1 = 99.92% and PC2 = 0.07%), indicating that the tea samples of FBT and MFBT could clearly be discriminated.…”
Section: Resultsmentioning
confidence: 93%
“…There are more than 100 types of terpenoid tea aroma substances, most of which are volatile monoterpenoids (such as geraniol and linalool) and sesquiterpenes (such as nerolidol) [ 34 , 58 ]. Studies have shown that volatile terpenes dominate the aroma (more than 60%) in tea products [ 59 , 60 ].…”
Section: Terpenoid Compounds In Tea Plantsmentioning
confidence: 99%
“…Generally speaking, β-myrcene, α-phellandrene, ( Z )-β-ocimene, ( Z )-furan linalool oxide, ( E )-furan linalool oxide, γ-terpinene, DMNT, cosmene, ( E )-pyranoid linalool oxide, linalool oxide pyranoside, linalyl formate, α-cubebene, γ-elemene, humulene, ( E )-β-famesene, ( Z , E )-α-farnesene, α-muurolene, α-farnesene, T-muurolol, α-cadinol, α-terpineol, geraniol, β-caryophyllen, δ-cadinene, ( E )-nerolidol, linalool, D-limonene, and β-pinene are reported to be important terpene compounds in tea aroma [ 48 , 59 , 61 ]. Among them, linalool and its furan oxides, ( Z )-furan linalool oxide and ( E )-furan linalool oxide, are important components of sweet and floral aromas, while ( E )-pyranoid linalool oxide and linalool oxide pyranoside have earthy aromas [ 62 ].…”
Section: Terpenoid Compounds In Tea Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by He et al (2022) distinguished different oolong tea cultivars. They correlated the e-nose data (FOX4000, Alpha MOS) and GC-MS with a headspace-solid phase microextraction method (HS-SPME-GC-MS) to explore the differences in aroma compounds and their effects on oolong tea cultivars suitability.…”
Section: Overview Of E-senses (Electronic Tongue and Nose)mentioning
confidence: 99%